Small‐cell neuroendocrine carcinoma of the cervix accompanied by adenocarcinoma and high‐grade squamous intraepithelial lesion. Issue 10 (2nd June 2022) - Okabe, Asako; Ishida, Mitsuaki; Noda, Yuri; Okano, Kimiaki; Sandoh, Kaori; Fukuda, Hisato; Kita, Masato; Okada, Hidetaka; Tsuta, Koji
Abstract: Few cytological reports have described small‐cell neuroendocrine carcinoma (SCNEC) in the female genital tract. In the present study, we describe a cytological case of SCNEC accompanied by adenocarcinoma, as well as high‐grade squamous intraepithelial lesion (HSIL). A Japanese woman (42 years old) presented with abnormal genital bleeding. A conventional Papanicolaou smear revealed an inflammatory condition with three neoplastic components: SCNEC as irregular aggregates of neoplastic small round cells with nuclear molding and granular chromatin; adenocarcinoma as columnar cell clusters with peripherally located large nuclei, and HSIL as sheets or clusters of dysplastic basal‐type squamous cells with irregular hyperchromatic nuclei. Accordingly, a cytodiagnosis of SCNEC with adenocarcinoma and HSIL was made. Owing to the rarity of cervical SCNEC, cytological diagnosis may be difficult. Due to its aggressive clinical behavior, the presence of an SCNEC component should be verified in any cytodiagnosis of adenocarcinoma or HSIL.